The influence of tax knowledge and tax sanctions on taxpayer compliance among individual employees with risk preferences as a moderating variable - Ledy Setiawati; Winalty Novaria Pardosi (Proceeding International Conference on Accounting and Finance, 2025)
This study aims to examine the influence of tax knowledge and tax sanctions on taxpayer compliance among individual employees registered at the Primary Tax Service Office (KPP Pratama) of Samarinda Ulu, with risk preferences as a moderating variable. In determining the sample, this study used purposive sampling, obtaining 100 respondents. This research is a combination of qualitative and quantitative methods, with primary data collected through a questionnaire. The questionnaire was distributed physically (offline), and the analysis tool used was SmartPLS 4.0. The results of this study indicate that both tax knowledge and tax sanctions have a positive and significant effect on taxpayer compliance among individual employees. Risk preferences as a moderator tend to weaken the relationship between tax knowledge and taxpayer compliance but strengthen the relationship between tax sanctions and taxpayer compliance among individual employees.